PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI - Navia, Yola; Asri, Yasnur; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThe research is aimed (1) to describe ability of writing biographical texts of students grade X at SMA Negeri 12 Padang before using inkuiri strategy, (2) to describe the ability of writing biographical texts of students grade X SMA Negeri 12 Padang after using inkuiri strategy, (3) to describe the effect of inkuiri strategy to words the ability of writing biographical texts of students grade X at SMA Negeri 12 Padang. This is quantitative research combines with experimental method. Based on data analysis, the use of cooperative integrated reading and composition learning model influences the ability of writing biographical texts of students grade at SMA Negeri 12 Padang.Kata kunci: pengaruh, strategi pembelajaran inkuiri, menulis teks biografi